The response of sedimentation regime to changes in upstream runoff, based on modelling scenarios analysis in Lingdingyang Estuary, China - Chen, Kanglin (Frontiers in Marine Science, 2025)
In recent decades, episodic extreme meteorological events have occurred frequently worldwide. Extreme drought and flood events have notably impacted on the evolution of large estuarine deltas, affecting estuarine geomorphology, human settlements, and infrastructure. However, understanding the impact of these extreme hydrological events on estuarine geomorphic evolution is hampered due to the lack of knowledge about event-based hydrodynamic mechanisms. Lingdingyang Estuary (LE), which is located in the central and southern part of the Pearl River Delta, southern China and has large number of records in extreme drought and catastrophic flood disasters from 1960s to 2010s, provides an opportunity to examine variations in estuarine deposition regime caused by such extreme hydrological events. A state-of-the-art modeling tool (TELEMAC-2D), was used to simulate geomorphic evolution in six scenarios, accounting for low upstream runoff (i.e. extreme drought) and high upstream runoff (i.e. catastrophic flood). This results revealed that: i) The deposition regime in the Inner-lingdingyang Estuary (ILE) altered from an erosion pattern under low upstream runoff conditions to a strong deposition pattern under high upstream runoff conditions, where the scale of upstream runoff and sediment delivery was of key importance. The deposition regime shift may occur at the upstream runoff conditions between 3120 m3/s and 6831 m3/s. ii) Under high upstream runoff conditions, large area of strong depocenters were easily formed outside the outlets, causing flood discharge block from outlets, which increased the risk of flooding. iii) The most prominent morphologic response to changes in upstream runoff was observed in the Western Shoal, i.e. a medium erosion pattern in the MQ1scenario (Extreme drought) and an extremely strong deposition pattern in the MQ5 scenario (Normal drought). The geomorphic balance (i.e., the state of net deposition volume approaching equilibrium) between the Western Shoal and the Western Channel requires critical consideration. iv) The sudden and substantial sedimentation was detected in the navigation channels, i.e. a net deposition volume of 1.22×106 m3 in the Eastern Channel under catastrophic flood conditions. During catastrophic flood, bathymetric monitoring should be implemented to guide mitigation measures, such as emergency necessary dredging operations. Finally, large-scale sand mining should be avoided in the whole Middle Shoal owing to its limited sediment deposition capacity (For example, the net deposition volume in the Middle shoal was found to be less than 10% of that in the Western Shoal and 65% of that in the Eastern Shoal under catastrophic flood). However, appropriate sand mining scheme can be performed in the Eastern Shoal due to the net deposition pattern under upstream various hydrological conditions. My findings are valuable to improve the scientific comprehensive management of LE and promote the high-quality development of the Guangdong-Hong Kong Macao Greater Bay Area. The insights obtained from this study can be comprehensively understand the morphological transition in LE and benefit other estuaries that are subject to similar experiences.